2020
DOI: 10.1155/2020/5083140
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and Associated Factors among Adolescent Girls in Damot Sore District, Southern Ethiopia

Abstract: Background. Adolescent girls were given little health and nutrition attention. Focusing on adolescent girls’ nutrition prior to conception is one way to break the intergenerational cycle of malnutrition. Therefore, the aim of this study was to assess the prevalence of undernutrition and associated factors among adolescent girls in rural Damot Sore District, Southern Ethiopia. Methods. A community-based cross-sectional study was conducted from Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
19
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 27 publications
6
19
2
Order By: Relevance
“…Stunting was higher among late adolescents (15–19 years) than early adolescents (10–14 years) and was more severe among late adolescent girls than their counterparts. The above finding is concordant with the previously available literature [ 18 , 31 ]. However, studies in other settings found different results [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…Stunting was higher among late adolescents (15–19 years) than early adolescents (10–14 years) and was more severe among late adolescent girls than their counterparts. The above finding is concordant with the previously available literature [ 18 , 31 ]. However, studies in other settings found different results [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…A lower level of parenteral education positively influenced the occurrence of being underweight among adolescent girls in other studies. 18,20 In line with these previous findings, we also found the paternal education primary or lower level increased the risk of thinness, possibly because parenteral education appears to play a crucial role in providing adequate quantities and qualities of food to children. 50,51 Family size has been shown to have both a positive and negative impact on children and adolescence nutritional status in some previous studies.- 52,53 We identified an increasing family size (>4) had higher odds of being underweight in our study subjects.…”
supporting
confidence: 90%
“…Adolescents (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years old) comprise one quarter of the world's population. 8,9 This time of life is critically important because it is during this period that rapid growth and development occurs, and thus, adolescents require higher nutrient intakes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations